ANALISIS TINGKAT KEPUASAN PENGUNJUNG TERHADAP FASILITAS DAN LAYANAN (STUDI KASUS DI CIKAO PARK TAHUN 2024) - Permana, Axel Adam; Wulandari, Astri (STABN Raden Wijaya Wonogiri, 2025)
This study aims to analyze visitor satisfaction with facilities and services in Cikao Park, Purwakarta. The method used in this study is a quantitative approach with a survey using a Likert scale of 1-4 to 100 respondents who havevisited Cikao Park. The data was analyzed using validity, reliability, and linear regression tests to measure the relationship between facilities and services to visitor satisfaction. The results of the study show that facilities and services have a significant influence on visitor satisfaction. This finding is expected to be the basis for tourist destination managers to improve the tourist experience through improving the quality of facilities and services.